Arteriovenous Passage Times and Visual Field Progression in Normal Tension Glaucoma - Eva Charlotte Koch; Kay Oliver Arend; Marion Bienert; Andreas Remky; Niklas Plange (The Scientific World Journal)
Purpose. Fluorescein angiographic studies revealed prolonged arteriovenous passage (AVP) times and increased fluorescein filling defects in normal tension glaucoma (NTG) compared to healthy controls. The purpose of this study was to correlate baseline AVP and fluorescein filling defects with visual field progression in patients with NTG. Patients and Methods. Patients with a follow-up period of at least 3 years and at least 4 visual field examinations were included in this retrospective study. Fluorescein angiography was performed at baseline using a confocal scanning laser ophthalmoscope (SLO, Rodenstock Instr.); fluorescein filling defects and AVP were measured by digital image analysis and dye dilution curves (25 Hz). Visual field progression was evaluated using regression analysis of the MD (Humphrey-Zeiss, SITA-24-2, MD progression per year (dB/year)). 72 patients with NTG were included, 44 patients in study 1 (fluorescein filling defects) and 28 patients in study 2 (AVP). Results. In study 1 (mean follow-up years, visual field tests), MD progression per year ( dB/year) was significantly correlated to the age (, ) but not to fluorescein filling defects, IOP, or MD at baseline. In study 2 (mean follow-up years, visual field tests), MD progression per year ( dB/year) was significantly correlated to AVP (, ) but not to age, IOP, or MD at baseline. Conclusion. Longer AVP times at baseline are correlated to visual field progression in NTG. Impaired retinal blood flow seems to be an important factor for glaucoma progression.